Optimizing the Management Function of the “LYN” City Transportation Route - Mahmudalia Rosa Yulaicho; Susi Hardjati (Universitas Muhammadiyah Gorontalo, 2022)
Joyoboyo intermodal terminal needs to get optimal management after undergoing revitalization due to the decrease in the number of city transportation. The purpose of this study was to determine the role of the Department of Transportation in optimizing the management function of the Lyn city transportation route at the Joyoboyo Intermodal Terminal, Surabaya. This study uses a qualitative descriptive method with a focus based on the public sector role theory from Jones, namely: the regulatory role, enabling role, and direct provision of goods and services. The results of the study stated that the role of the Transportation Department in Surabaya was quite optimal in optimizing the management function of the Lyn city transportation route, characterized by: 1) regulatory role, through the preparation of control programs, renewal of the retribution payment system, division of route lanes, and rejuvenation of the transportation fleet in accordance with regulations. determined so that the role is carried out optimally. 2) enabling role, through the implementation of the control program, renewal of the retribution payment system, division of route lanes, and rejuvenation of the designated transportation fleet, the obstacles faced were caused by the decline in passengers, so that the implementation of the role was quite optimal. 3) direct provision of goods and services, through evaluation meetings and listening to driver complaints as a form of supervision and control role is carried out quite optimally, because the transportation fleet rejuvenation program is still lacking in coordination with city transportation drivers